Analysis of the forms of association /cooperation in Romania - Ancuţa Marin; Petruţa Turek-Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
This paper analyzes the evolution of the modern agrarian associations and cooperatives in Romania. Right now, our country is far behind the west-european countries regarding the development of the associative sector in the agricultural domain, from the diversity point of view and also from the presence on the market. One of the biggest problems of the small farmers from Romania represents selling the production, the traditional markets are being suffocated many times by agents. The agrarian sector is confrunting with problems marked mainly by the poor organization of the farmers regarding the production marketing and a slow structuring of their commercial behavior. The biggest problem of the agrarian cooperatives in Romania is the access to funding. This is due to the business related problems and their specific legal form. In Romania a law for crediting cooperatives doesn't exist, they are not found in the bank nomenclature and they are treated like any LLC. Also, there is an accute need for founding a high level training program intended for the agrarian cooperatives and associations leaders. The purpose is to present a current state synthesis in order to have a real image of their situation. The main object of this study is to make an assessment of the agrarian cooperatives's situation in Romania with the purpose of offering solutions and recommendations, by setting the development directions in order to become compatible with the European systems of agrarian cooperatives.
Keywords: 330; association forms; agrarian cooperatives; agrarian associations; producer groups